Frontline Mongolian Healthcare Professionals and Adverse Mental Health Conditions During the Peak of COVID-19 Pandemic - Tsogbadrakh, Basbish; Yanjmaa, Enkhjargal; Badamdorj, Oyungoo; Choijiljav, Dorjderem; Gendenjamts, Enkhjargal; Ayush, Oyun-erdene; Pojin, Odonjil; Davaakhuu, Battogtokh; Sukhbat, Tuya; Dovdon, Baigalmaa; Davaasuren, Oyunsuren; Stark, Azadeh (Frontiers in Psychology, 2022)
Background: The relatively young and inexperienced healthcare professionals in Mongolia faced with an unprecedent service demand in response to the COVID-19 pandemic. Due to the small size of the healthcare workforce the Mongolian Health Ministry had no choice but to mandate continuous and long workhours from the healthcare workforce. Many of the healthcare professionals exhibited signs and symptoms of mental health disorders. This study aimed to discern the prevalence various mental health concerns, i.e., depression, anxiety and stress, insomnia, and to discern the factors that increased susceptibility to mental health disorders among frontline healthcare professionals providing healthcare services for COVID-19 patients in Mongolia. Methods: A Cross-sectional research design was implemented. We collected data from 965 healthcare professional, randomly selected from 18 government hospitals, in four regions of Mongolia. Data were collected using the Depression Anxiety Stress -21, the General Self-Efficacy Scale, and the Insomnia Severity Index instruments. We constructed the scale of Pandemic Response Symptoms (PaReSy) which captured stress, depression, and anxiety. Data were analyzed using descriptive statistics, Kruskal-Wallis statistical test and multinominal logistic regression analysis. Results: Prevalence of depression (52.3%, CI 95%: 49.1%-55.5%), anxiety (70.2%, CI 95%: 67.2%-73.0%) and stress (35.8%, CI 95%: 32.7%-38.9%) was documented among Mongolian healthcare professionals. Perception of self-efficacy reduced susceptibility to PaReSy either at mild/moderate (OR=.948, 95%CI=.911-0.988, P=.011) or severe/extremely severe level (OR=.911, 95%CI=.861-.963, P=.001). Within each stratum of insomnia, the risk of experiencing PaReSy increased almost linearly both in the category of mild/moderate PaReSy and in the category of severe/extremely severe PaReSy. Conclusion: Improving self-efficacy and sleeping quality assist healthcare workers to manage depression, anxiety, and stress. Findings provide important evidence to implement measures and strategies to assist healthcare professionals in low- and middle-income countries to constructively address their mental health concerns and needs. Keywords: Depression, anxiety, stress, psychological wellbeing, self-efficacy, insomnia, COVID-19